Experimental Analysis of the Dynamic Response of Saturated Clayey Soil Under Impact Loading - Ahmed, B. A.; Rasheed, A. H. (Engineering, Technology & Applied Science Research, 2022)
The impact of loads on machine foundations is a typical cause of vibrations in industrial applications. Typically, these foundations will transfer vertical dynamic loads to the surface, which will result in earth vibrations that may cause structural damage to nearby structures. Dynamic impacts can vary from significant failure of sensitive sensors or systems to evident structural damage. The current work investigates the behavior of saturated clay soil under a single impulsive load. Deflectometry via falling weights was conducted to produce single pulse energy by dropping different weights from various elevations. The reactions of soils at various places were investigated (vertical displacement at topsoil surface). Such reactions consist of displacements, velocities, and accelerations caused by the impact occurring at the surface depth. The maximum displacement reaction of stiff soil was reduced by 80% in comparison with soft soil under the same impact load. The average percentage of change for stiff soil was 49% larger than for soft soil, as a result of kinetic energy caused by an increased contact surface. Maximum displacements increased with increasing operational frequency and dynamic load.